ANALISIS STRUKTURALISME DALAM NOVEL â€œWARISAN MASA SILAMâ€ KARYA V. LESTARI - Sukarismanti, sukarismanti; Najamudin; Sukarismanti (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2023)
A novel is an art form that is used to convey messages and meanings to readers or viewers by language. However, understanding its message requires an approach. One approach that can be used is the structuralism approach. Therefore, the main objective of this study is to understand how the narrative structure in the novel influences the meaning and message that the author wants to convey. This study will use the method of structuralism analysis to identify important elements in the novel, such as characters, plot, setting, theme, etc., and how these elements are interrelated and influence the meaning and message to be conveyed. This analysis reveals that the analysis of structuralism in the novel